Effects of borneol on the pharmacokinetics of 9-nitrocamptothecin encapsulated in PLGA nanoparticles with different size via oral administration. (21st November 2016) - Ru, Ge; Han, Limei; Qing, Jin; Sheng, Jianyong; Li, Ruixiang; Qiu, Mingfeng; Wang, Jianxin
Abstract: Context : Although nanocarriers provide promising potential for oral drug delivery, the delivery efficiency remains unsatisfactory and needs to be improved. Size is considered to be the most important characteristic of nanoparticles related to their oral absorption. Borneol has been proved to have the ability to enhance the penetration and transport of many drugs through various physical barriers. Objective : To investigate the effect of the particle size and coadministration of borneol on the pharmacokinetics and bioavailability of entrapped drug in different size poly(lactic-co-glycolic acid) (PLGA) nanoparticles. Materials and methods : 9-Nitrocamptothecin (9-NC)-loaded PLGA nanoparticles with three different range of size (50–100 nm, 100–200 nm, 200–300 nm) were prepared by emulsion solvent-evaporation method. The pharmacokinetic study in rats of these nanoparticles with borneol was carried out. Results : The experiments showed that the encapsulation drug in nanoparticles with size below 200 nm could improve the oral bioavailability of 9-NC. The small size nanoparticles (50–100 nm) had a better improvement efficacy. As for borneol, it played a significant promotion effect only on the small nanoparticles. Moreover, there was no significant influence on the nanoparticles with size more than 100 nm. Discussion and conclusion : The study indicated that both entrapping drug in nanoparticles with the size below 100 nm and coadministrating with borneol could enhance the gastrointestinal absorption of water insoluble drug. The combination of the two strategies provides a potential approach to improve the oral bioavailability of drug.